Disclosure of clinically actionable genetic variants to thoracic aortic dissection biobank participants - Adelyn Beil; Whitney Hornsby; Wendy R. Uhlmann; Rajani Aatre; Patricia Arscott; Brooke Wolford; Kim A. Eagle; Bo Yang; Jennifer McNamara; Cristen Willer; J. Scott Roberts (BMC, 2021)
Abstract Background Disclosure of pathogenic variants to thoracic aortic dissection biobank participants was implemented. The impact and costs, including confirmatory genetic testing in a Clinical Laboratory Improvement Amendments (CLIA)-certified laboratory, were evaluated. Methods We exome sequenced 240 cases with thoracic aortic dissection and 258 controls, then examined 11 aortopathy genes. Pathogenic variants in 6 aortopathy genes (COL3A1, FBN1, LOX, PRKG1, SMAD3, and TGFBR2) were identified in 26 participants, representing 10.8% of the cohort (26/240). A second research sample was used to validate the initial findings. Mailed letters to participants disclosed that a potentially disease causing DNA alteration had been identified (neither the gene nor variant was disclosed). Participants were offered clinical genetic counseling and confirmatory genetic testing in a CLIA laboratory. Results Excluding 6 participants who were deceased or lost to follow-up, 20 participants received the disclosure letter, 10 of whom proceeded with genetic counseling, confirmatory genetic testing, and enrolled in a survey study. Participants reported satisfaction with the letter (4.2 ± 0.7) and genetic counseling (4.4 ± 0.4; [out of 5, respectively]). The psychosocial impact was characterized by low decisional regret (11.5 ± 11.6) and distress (16.0 ± 4.2, [out of 100, respectively]). The average cost for 26 participants was $400, including validation and sending letters. The average cost for those who received genetic counseling and CLIA laboratory confirmation was $605. Conclusions Participants were satisfied with the return of clinically significant biobank genetic results and CLIA laboratory testing; however, the process required significant time and resources. These findings illustrate the trade-offs involved for researchers considering returning research genetic results.